![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/(2.x-5)+17=6
=> 2x - 5 = -11
=> 2x = -6
=> x = 3
vậy_
2/10-2.(4-3x)=-4
=> 2(4 - 3x) = 14
=> 4 - 3x = 7
=> 3x = -3
=> x = -1
3/-12+3.(-x+7)=-18
=> 3(-x+7) = -6
=> -x+7 = -2
=> -x = -9
=> x = 9
4/24:(3.x-2)=-3
=> 3x - 2 = -8
=> 3x = -6
=> x = -2
5/-45:5.(-3-2.x)=3
=> 5(-3 - 2x) = -15
=> -3 - 2x = -3
=> - 2x = 0
=> x = 0
6/x.(x+7)=0
=> x = 0 hoặc x + 7 = 0
=> x = 0 hoặc x = -7
7/(x+12).(x-3)=0
=> x + 12 = 0 hoặc x - 3 = 0
=> x = -12 hoặc x = 3
8/(-x+5).(3-x)=0
=> -x + 5 = 0 hoặc 3 - x = 0
=> x = 5 hoặc x = 3
9/x.(2+x).(7-x)=0
=> x = 0 hoặc 2 + x = 0 hoặc 7 - x = 0
=> x = 0 hoặc x = -2 hoặc x = 7
10/(x-1).(x+2).(-x-3)=0
=> x - 1 = 0 hoặc x + 2 = 0 hoặc -x-3 = 0
=> x = 1 hoặc x = -2 hoặc x = -3
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 5.( x - 6 ) - 2.( x + 9 ) = 21
5x - 30 - 2x - 18 = 21
3x - 48 = 21
3x = 21 + 48
3x = 69
x = 23
2) 2.( x + 3 ) + 3.( x + 1 ) = 15 - ( - 9 )
2x + 6 + 3x + 3 = 24
5x + 9 = 24
5x = 24 - 9
5x = 15
x = 3
3) ( - x + 5 ).(3 - x ) = 0
=> - x + 5 = 0 hoặc 3 - x = 0
=> x = 5 hoặc x = 3
4) ( x - 12 ) - 15 = ( 20 - 7 ) - ( 18 + x )
x - 12 - 15 = 13 - 18 - x
x - 27 = - 5 - x
x + x = - 5 + 27
2x = 22
x = 11
5) x - ( 17 - 8 ) = 5 + ( 10 - 3x )
x - 9 = 5 + 10 - 3x
x + 3x = 15 + 9
4x = 24
x = 6
![](https://rs.olm.vn/images/avt/0.png?1311)
\((x-6)(3x-9)>0\)
TH1:
\(\orbr{\begin{cases}x-6< 0\\3x-9< 0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x< 6\\x< 3\end{cases}}\)\(\Rightarrow x< 3\)
TH2:
\(\orbr{\begin{cases}x-6>0\\3x-9>0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x>6\\x>3\end{cases}}\)\(\Rightarrow x>6\)
Vậy \(x< 3\) hoặc \(x>6\)thì \((x-6)(3x-9)>0\)
Học tốt!
20.
\((2x-1)(6-x)>0\)
TH1:
\(\orbr{\begin{cases}2x-1>0\\6-x>0\end{cases}\Rightarrow\orbr{\begin{cases}x< \frac{1}{2}\\x< 6\end{cases}}\Rightarrow x< 6}\)
TH2
\(\orbr{\begin{cases}2x-1< 0\\6-x< 0\end{cases}\Rightarrow\orbr{\begin{cases}x>\frac{1}{2}\\x>6\end{cases}}\Rightarrow x>\frac{1}{2}}\)
Vậy \(x< 6\)hoặc \(x>\frac{1}{2}\)thì \((2x-1)(6-x)>0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(-65-\left(x+15\right)+105=0\)
\(-65-\left(x+15\right)=-105\)
\(x+15=-65-\left(-105\right)\)
\(x+15=40\)
\(x=25\)
b) |-6| + (-9) - (x+1) = 7
-3- (x+1) =7
x+1 = -10
x = -11
c)\(\left|5-x\right|+\left(-25+7\right)=-3-\left(-10\right)\)
\(\left|5-x\right|+\left(-18\right)=7\)
\(\left|5-x\right|=25\)
\(\Rightarrow\orbr{\begin{cases}5-x=25\\5-x=-25\end{cases}\Rightarrow\orbr{\begin{cases}x=-20\\x=30\end{cases}}}\)
d) \(28-\left|x+6\right|+\left(-2\right)=0\)
\(28-\left|x+6\right|=2\)
\(\left|x+6\right|=26\)
\(\Rightarrow\orbr{\begin{cases}x+6=26\\x+6=-26\end{cases}\Rightarrow\orbr{\begin{cases}x=20\\x=-32\end{cases}}}\)
e) \(x-\left(13-15\right)=5+\left(10-x\right)-\left(-1\right)\)
\(x+2=5+10-x+1\)
\(x+2=16-x\)
\(x+x=16-2\)
\(2x=14\)
\(x=7\)
f) \(-120-\left(x-5\right)=125\)
\(x-5=-120-125\)
\(x-5=-245\)
\(x=-240\)
g) \(10-\left(-5+2\right)+\left(-9\right)=\left(-20+7\right)-x\)
\(-16=-13-x\)
\(x=-13+16\)
\(x=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x - 7) + 17 = 6
=> 2x - 7 = 6 - 17
=> 2x - 7 = -11
=> 2x = -11 + 7
=> 2x = -4
=> x = -4 : 2
=> x = -2
+) 12 -2(3 - 3x)= -2
=> 2(3 - 3x) = 12 + 2
=> 2(3 - 3x) = 14
=> 3 - 3x = 14 : 2
=> 3 - 3x = 7
=> 3x = 3 - 7
=> 3x = -4
=> x = -4/3
\(\left(x+1\right)\left(x-3\right)=0\)
=> \(\orbr{\begin{cases}x+1=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-1\\x=3\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,-7x+7=21\)
\(\Rightarrow-7x=21-7=14\)
\(\Rightarrow x=-2\)
\(b,9x+11=20x+66\)
\(\Rightarrow9x-20x=66-11=55\)
\(\Rightarrow-11x=55\)
\(\Rightarrow x=-5\)
\(c,3^3.x+4^2=5^2.x-2.\left(2017\right)^0\)
\(27x+16=25x-2\)
\(\Rightarrow16+2=25x-27x=-2x\)
\(\Rightarrow-2x=18\)
\(\Rightarrow x=-9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ Suy ra: -35 + 7x - 2x + 20 = 15
5x - 15 = 15
5x = 30
x = 6
2/ Suy ra: 4x - 20 - 3x - 21 = -19
x - 41 = -19
x = 22
3/ Suy ra: 8 - 4x + 3x - 15 = 14
-7 -x = 14
x = -7 -14
x = -21
4/ Suy ra: 7x - 63 - 30 + 5x = -6 + 11x
7x + 5x - 11x = -6 +63 + 30
x = 87
5/ Suy ra: -21x +35 + 14x - 28 = 28
-21x + 14x = 28 +28 - 35
-7x = 21
x= -3
6/ Suy ra: 20 - 5x + 7x - 14 = -2
2x = -8
x = -4
7/ Suy ra: 4x +15 -5x = 7
-x = -8
x = 8
8/ Suy ra: 5x - 35 +30 -10x = 20
-5x - 5 = 20
-5x = 25
x = -5
9/ Suy ra: 35 - 7x + 5x - 10 = 15
-7x + 5x = 15 +10 - 35
-2x = -10
x = 5
3 . x - 5 = -20
=> 3 . x = -20 + 5
=> 3 . x = -15
=> x = -15 : 3
=> x = -5
2 . x - (-3) = 7
=> 2 . x + 3 = 7
=> 2 . x = 7 - 3
=> 2 . x = 4
=> x = 4 : 2
=> x = 2
(x - 5) . (x + 6) = 0
=> \(\orbr{\begin{cases}x-5=0\\x+6=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0+5\\x=0-6\end{cases}}\)
=> \(\orbr{\begin{cases}x=5\\x=-6\end{cases}}\)
|x| - 10 = -3
=> |x| = -3 + 10
=> |x| = 7
=> \(\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
Ta có : 3x - 5 = -20
=> 3x = -15
=> x = -15 : 3
=> x = -5